2006
DOI: 10.1029/2006gl026125
|View full text |Cite
|
Sign up to set email alerts
|

Size distribution of submarine landslides and its implication to tsunami hazard in Puerto Rico

Abstract: We have established for the first time a size frequency distribution for carbonate submarine slope failures. Using detailed bathymetry along the northern edge of the carbonate platform north of Puerto Rico, we show that the cumulative distribution of slope failure volumes follows a power‐law distribution. The power‐law exponent of this distribution is similar to those for rock falls on land, commensurate with their interpreted failure mode. The carbonate volume distribution and its associated volume‐area relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 24 publications
3
95
2
Order By: Relevance
“…Furthermore, the power law relationship between landslide area and volume is characterised by an exponent of 1.3 (Fig. 3a), which is similar to that obtained by ten Brink et al (2006) for slides in layered limestones, and higher than that obtained by Issler et al (2005) for clay-rich debris flows. This exponent indicates deeper excavation of material by the larger slope failures in the CS canyons.…”
Section: Nature Of Landslidessupporting
confidence: 77%
“…Furthermore, the power law relationship between landslide area and volume is characterised by an exponent of 1.3 (Fig. 3a), which is similar to that obtained by ten Brink et al (2006) for slides in layered limestones, and higher than that obtained by Issler et al (2005) for clay-rich debris flows. This exponent indicates deeper excavation of material by the larger slope failures in the CS canyons.…”
Section: Nature Of Landslidessupporting
confidence: 77%
“…The quantification of landslide volume is important to determine landslide susceptibility and hazard (Guzzetti et al, 2009), and also to support post-event mitigation actions, such as sediment control measures (Galiatsatos et al, 2007;Takara et al, 2010). Although crucial, the determination of landslide volume is not as straightforward as the quantification of the number of landslides (Malamud et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The difficulty resides in acquiring information on surface and sub-surface geometry for a large number of landslides, and can only be solved, at present, adopting empirical relations that link geometrical measurements, such as the individual landslide area, with its volume. Several authors have suggested that there is a relationship between the area and the volume of landslides that can be expressed through empirical formulations (Simonett, 1967;Rice and Fogging, 1971;Innes, 1983;Guthrie and Evans, 2004;Korup, 2005;ten Brink et al, 2006;Imaizumi and Sidle, 2007;Guzzetti et al, 2008;Imaizumi et al. 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In some cases the thickness of the deposit was clearly imaged, however in others a highly-reflective seafloor did not allow sub-bottom penetration, and in some cases the base of the deposits may have been deeper than could be penetrated by the profiling system. These data and interpretations were incorporated into a GIS where the volumes of landslide deposits were calculated based on estimates of the average thickness of the deposit and its areal extent, while the volumes of source areas of a subset of the mapped slides were calculated using the bathymetry and an interpolated smooth-surface technique reported by ten Brink et al (2006).…”
Section: Discussionmentioning
confidence: 99%